Notary's Responsibility for Signing A Blank Deed of Agreement - Farahiani, Sita; Handayani, Sri Wahyu (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The background is the practice of agreements for building shophouses which are stated in the Deed of Agreement through blank forms made before a Notary. The issue that arises then is whether the agreement can be accepted in positive law. The problem in this journal discusses how the Notary's Responsibility for the Deed of Agreement through blank forms and How the Legal Protection for the injured party is for the Deed that is canceled, which aims to gain an understanding regarding the validity of the Deed of Agreement. The method used is Normative Jurisprudence, Conceptual Approach Type, Using Data Collection Methods with Literature studies related to Laws and Regulations, and the Research Specifications used are Descriptive Techniques that focus on solving legal problems and events. The results of this study explain that the Notary's responsibility in making a deed of agreement through blank forms is very large, including civil, criminal, and administrative responsibilities. Legal protection for parties to a deed of agreement that is canceled by law is based on the principle of justice and legal certainty guaranteed by statutory regulations.